Paciente de sexo femenino de 45 años de edad con diabetes mellitus tipo 2. - Candelario Quisintuña, Meliza Brillid (2020)
Type 2 diabetes mellitus is a disease with really important global growth, its complications represent a major health problem worldwide because of its high prevalence of mortality. The goal of this clinical case is to avoid complications of diabetes mellitus through the nutritional care process. This clinical case includes a 45-year-old female patient diagnosed with two-year-old type 2 diabetes mellitus, in pharmacological treatment with metformin of 1500mg daily, goes for a routine medical check, through nutritional assessment it is determined that the patient presents his fasting glucose biochemical values of 181mg/dl and a glycosylated hemoglobin of 7.9%, excessive carbohydrate intake as measured by the 24-hour reminder. Through the monitoring and monitoring of 3 months very good results are shown, mainly in biochemical values, managing to reduce glucose values to 110mg/dl and glycosylated hemoglobin to 5.5%. Poor diabetes control is mainly caused by poor diet, complications of diabetes mellitus have been avoided through the nutritional care process applied in the present case, the patient had good adherence to treatment.